Future land carbon removals in China consistent with national inventory - Yue He; Shilong Piao; Philippe Ciais; Hao Xu; Thomas Gasser (Nature Communications)
Abstract China’s commitment to carbon neutrality by 2060 relies on the Land Use, Land-Use Change, and Forestry (LULUCF) sector, with forestation targets designed to enhance carbon removal. However, the exact sequestration potential of these initiatives remains uncertain due to differing accounting conventions between national inventories and scientific assessments. Here, we reconcile both estimates and reassess LULUCF carbon fluxes up to 2100, using a spatially explicit bookkeeping model, state-of-the-art historical data, and national forestation targets. We simulate a carbon sink of −0.24 ± 0.03 Gt C yr−1 over 1994–2018 from past forestation efforts, aligned well with the national inventory. Should the official forestation targets be followed and extended, this could reach −0.35 ± 0.04 Gt C yr−1 in 2060, offsetting 43 ± 4% of anticipated residual fossil CO2 emissions. Our findings confirm the key role of LULUCF in carbon sequestration, but its potential will decline if forestation efforts cease, highlighting the necessity for emission reductions in other sectors to achieve carbon neutrality.